MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KOMUNIKASI DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL ANGKASA - norazmi sari; Ahmad Suriansyah; Ratna Purwanti (STKIP Subang, 2025)
This study was motivated by the low levels of students’ critical thinking skills, communication abilities, and learning outcomes in Pancasila Education. This issue was caused by one-way teaching methods and a lack of variety in learning models, which made it difficult for students to understand the material and communicate effectively. The proposed solution was the implementation of the ANGKASA model. This research is a Classroom Action Research (CAR) conducted over three sessions, involving 18 fifth-grade students at SDN Anjir Muara Lama during the second semester of the 2024/2025 academic year. Qualitative data were obtained through observations of teacher and student activities, as well as assessments of students’ critical thinking and communication skills. Quantitative data were collected from students’ written test results. The data were analyzed descriptively using cross-tabulation and presented in the form of tables, graphs, and percentages. The results showed significant improvement in all aspects: teacher activity increased from 79% to 96%, student activity from 56% to 100%, critical thinking skills from 22% to 89%, communication skills from 44% to 100%, summative learning mastery from 67% to 100%, and formative learning mastery from 70% to 100%. Therefore, the ANGKASA model proved to be effective in enhancing learning activities.